EFFECT OF A COMBINED EXERCISE AND MAGNESIUM SUPPLEMENTATION REGIMEN ON BLOOD PRESSURE IN GRADE I HYPERTENSIVE ADULTS - Boit, Dr. Edwin Kiptolo; Theuri, Dr. Gitahi; Ogweno, Dr. Gordon (Journal of Health, Medicine and Nursing, 2020)
Purpose: The main aim of the study was to assess the change in resting Blood Pressure (BP) after a 6 week combined exercise and magnesium (Mg) supplementation regimen in grade I hypertensive adults. The secondary aim of the study was to assess the change in resting Heart Rate (HR) after a 6 week combined exercise and magnesium supplementation regimen in grade I hypertensive adults. Methodology: This study employed an experimental research design because specific conditions were controlled and its effects observed. In this case, exercise and administration of Mg was controlled by the researcher and the influences on resting BP and RHR were observed. A sample of 14 hypertensive adults was used in the study. Data was analyzed using SPSS version 25 (IBM Limited, UK, 2017) and Microsoft Excel 2013 for Windows. The significance level was set at p<0.05. Data was tested for normal distribution using the Shapiro-Wilk test while the Levenes test was used to test for data normality. Data was determined to be parametric. A paired t-test was used to compare mean differences from baseline, mid-point and post-test within the group. Results: There was no significant difference observed at baseline for Systolic Blood Pressure (SBP) and Diastolic Blood Pressure (DBP) within the exercise and magnesium supplementation group (EMG) (p>0.05). The EMG had a mean SBP and DBP of 145.7 ± 6.4 mmHg and 88.9 ±5.9 mmHg at baseline. Following a combination of exercise (45 min, 5 times a week) and magnesium supplementation (500 mg/day) the mean SBP and DBP reduced by -3.6 ± 3.2 mmHg and -3.4 ± 5.1 mmHg respectively after 3 weeks and reduced further by -7.1 ± 2.1 mmHg and -4.9 ± 4.4mmHg after 6 weeks. The changes were statistically significant (p<0.05) for SBP after 3weeks but not for DBP (p>0.05). The changes were statistically significant (p<0.05) for both SBP and DBP after 6 weeks. In addition, there was no significant difference observed at baseline for RHR within the EMG group (p>0.05).The EMG group had a mean RHR of 82.2 ± 10.7 bpm at baseline. Following a combination of exercise (45 min, 5 times a week) and magnesium supplementation (500 mg/day) the mean RHR reduced by -4.8 ± 5.9 bpm after 3 weeks and reduced further by -10.9 ± 4.0 bpm after 6 weeks. The changes were statistically significant (p<0.05) after 3 weeks and 6 weeks respectively. Recommendations for practice and policy: The study findings suggests that a combination of exercise and magnesium supplementation is an alternative non-pharmacological BP management method for individuals with hypertension, therefore exercise and magnesium supplementation could be included as part of the treatment protocol for individuals with hypertension